Evaluating trends in recruitment challenges in vape shop research, e-cigarette product characteristics and use among shop customers from 2019 to 2023: A mixed-methods study - Jimi Huh; Artur Galimov; Leah Meza; Ellen Galstyan; Jennifer B. Unger; Lourdes Baezconde-Garbanati; Steven Sussman (Tobacco Induced Diseases, 2024)
Introduction Brick-and-mortar vape shops specialize in the sale of e-cigarettes and remain a primary source for purchasing emerging e-cigarette products. New regulatory policies have been implemented at local-, state- and federal-level; the retail environment at vape shops and product preferences among vape shop customers shifted accordingly.